Circulating corticosterone predicts near-term, while H/L ratio predicts long-term, survival in a long-lived seabird - Maness, Terri J.; Grace, Jacquelyn K.; Hirchak, Michael R.; Tompkins, Emily M.; Anderson, David J. (Frontiers in Ecology and Evolution, 2023)
Assessing stress in wild populations is important in many ecological and conservation contexts because physiological responses of individuals to stressors can be used to identify at-risk populations and the ability to respond appropriately to stressors is related to individual quality and fitness. Yet, one of the great challenges in ecophysiology is linking physiological measures in wild animal populations with changes in individual fitness. Here, we examined two indices of stress, circulating baseline corticosterone concentration ([Cort]) and heterophil:lymphocyte (H/L) ratio, in a long-lived seabird, the Nazca booby (Sula granti) and their relationship with current individual state and subsequent survival and lifetime reproductive success. [Cort] was related to sex, age, and current reproductive effort in that males, older, and currently breeding birds had higher [Cort]. [Cort] was negatively associated with survival to the next breeding season. H/L ratio was not associated with the current state of birds, but predicted long-term survival. These findings suggest that H/L ratio may be a better indicator of overall fitness than [Cort] in this species and we propose the H/L (or neutrophil/lymphocyte) ratio-Fitness Hypothesis which posits that these ratios are repeatable within individuals and are negatively associated with fitness. As such, these ratios could be a powerful monitoring tool for assessing population health or identifying at-risk populations.